Major obstetric hemorrhage: Patients' perspective on the quality of care. (May 2018) - de Visser, Suzan M.; Kirchner, Christian A.; van der Velden, Bianca G.J.; de Wit, Alexander C.; Dijkman, Anneke; Huisjes, Anjoke J.M.; Middeldorp, Johanna M.; Moonen-Delarue, Desirée; van Dillen, Jeroen; Vandenbussche, Frank P.H.A.; Hulscher, Marlies E.; Scheepers, Hubertina C.J.; et al.
Abstract: Objectives: Major obstetric hemorrhage (MOH) is the leading cause of severe maternal morbidity and mortality, and can have a significant impact on a woman's life. This study aims to gain insight into the patients reported experiences (PREs) and outcomes (PROs) after a major obstetric hemorrhage, and to investigate which patients are most at risk for negative experiences. Material and methods: A Consumer Assessment of Healthcare Providers and Systems (CAHPS) based questionnaire was developed covering items on the PREs and PROs, and send to all patients with blood loss exceeding 2500 ml in six hospitals over the period of 2008–2012. A regression analysis was performed to find determinants for negative experiences. Results: In total 372 of the 570 questionnaires were returned. Women scored the overall care before, during and after the MOH with a mean of 7.67, 7.62 and 7.28, respectively. However, most PRE items individually were scored suboptimal, with items regarding information supply scoring the lowest. Our results on the PROs showed 81% of the women (362) sustaining extreme fatigue, whereas problems with concentration (53% of 373 women), memory (49% of 353), or reliving (49% of 356) and irritability (51% of 355) were also frequently endured. Negative long term effects were observed in 28% of the women (106 of 372). We found 'year of the MOH longer ago', 'a lower total blood loss' and 'a large location of birth' to be determinants for negative experiences. Conclusions: Women frequently reported negative experiences and outcomes following a MOH. Information supply after an MOH concerning both physical and psychological complaints is essential for the improvement of care.